Relationships between counsellor interventions, client experiencing, and emotional expressiveness: An exploratory study - Stalikas, Anastassios; Fitzpatrick, Marilyn (Canadian Journal of Counselling and Psychotherapy, 2007)
The importance of client emotionality in counselling, while much discussed by theorists, has been less well investigated by researchers. The relationship between counsellor interventions that occur with particular levels of emotional arousal and experiencing has not been fully investigated. This study examined the relationship between client experiencing, strength of feeling, and counsellor verbal response modes in three different types of counselling. No evidence of a significant association between counsellor verbal response modes and levels of experiencing or strength of feeling was found. The meaning of this finding and its implications for counsellors and researchers are discussed.